Explosion box Based on Scientific approach to Improve Knowledge and Compliance in Consuming Iron Supplements - Adisurya Saputra; Taufik Hidayat; Rita Aprianti; Sri Erliani (Sarana Ilmu Indonesia (salnesia), 2026)
One educational tool that can be used to convey health information is the “explosion box”, an interactive learning tool in the form of a layered box that presents material in a visually engaging way. Low adherence to iron supplement intake is often caused by a lack of understanding regarding the importance of preventing anemia. An explosion box based on a scientific approach has the potential to be an effective educational tool because it combines elements of surprise and interactivity to enhance adolescent girls’ knowledge regarding anemia prevention and foster critical thinking. This study aimed to measure the effectiveness of this medium on knowledge and adherence to iron supplement intake among adolescent girls. The method used was a pre-experimental study with a one-group pretest-posttest design. The study subjects consisted of 37 adolescent girls, selected using total sampling. The results showed a significant increase in knowledge (p-value <0.001) and adherence (p-value 0.003) following the intervention using the explosion box based on a scientific approach. Thus, this medium proved effective in improving knowledge and adherence to iron supplement consumption among adolescent girls. An “explosion box” based on a scientific approach was expected to serve as an educational resource in efforts to prevent anemia among adolescent girls.